“We Will Appreciate Each Other More After This”: Teachers' Construction of Collective and Personal Identities During Lockdown - Spicksley, Kathryn; Kington, Alison; Watkins, Maxine (Frontiers in Psychology, 2021)
In March 2020, schools in England were closed to all but vulnerable children and the children of key workers, as part of a national effort to curb the spread of the Covid-19 virus. Many teachers were required to work from home as remote learning was implemented. Teaching is primarily a relational profession, and previous literature acknowledges that supportive relationships with peers help to maintain teachers’ resilience and commitment during challenging periods. This paper reports on findings from a small-scale study conducted in England during the first national lockdown beginning in March 2020, which explored the impact of the requirement to teach remotely on teachers’ identity and peer relationships. A discourse analysis, informed by the aims and practices of discursive psychology, was conducted in order to explore the association between constructions of peer support and responses to the Covid-19 pandemic. Findings indicate that teachers who presented their professional self-identity as collective rather than personal appeared to have a more positive perspective on the difficulties caused by the Covid-19 pandemic. These findings, which have implications for policymakers and school leaders, contribute to the growing field of research on the impact of the Covid-19 pandemic on education by showing the strong association between teachers’ constructions of identity and their capacity to respond positively to the challenges brought about by the Covid-19 pandemic.